Lived Experiences of the Public-School Teachers in the Implementation of Matatag Curriculum (London Journal of Research In Humanities and Social Sciences, 2025)
The MATATAG Curriculum represents a significant reform in the Philippine education system, aiming to enhance the K to 12 Basic Education Program by addressing persistent challenges. This study aims to explore lived experiences of the nine (9) public-school teachers in the implementation of MATATAG curriculum in the Department of Education Cebu Province for the academic year 2024-2025. The focused of this study centered on the qualitative study with which methodology was associated with Husserl’s philosophy of descriptive phenomenological research on the lived experiences of the public-school teachers representing three teachers per grade level in DepEd Cebu Province. The use of thematic analysis was utilized based on the experiences of the participants to generate emergent themes. The Positive Experiences are as follows: Relevant and well-aligned to expected outcomes, Student-centered approach, Striving to stay motivated despite resource constraints, Training is helpful for implementation and Adapting teaching strategies to suit changing needs while for the Negative Experiences are Limited materials and resources hindering effective teaching, Slow internet connectivity and struggles with accessing materials, Limited 10-day training perceived as inadequate for practical application, Decreased motivation due to lack of readiness and resource constraints, and Content not suitable for learners in upland. The implementation of the MATATAG Curriculum in upland schools has faced positive and challenging experience for educators and requires more training, planning on preparation and resource allocation. The school may have a more training period to provide educators with a deeper understanding of the curriculum and practical strategies for implementation, allocate additional resources and teaching materials tailored to the unique needs of upland learners and lastly, a comparison on experiences of teachers towards the MATATAG curriculum in upland and in road schools.
Keywords: totalitarianism; Croatia; Yugoslavia; Croatian Spring; Praxis; Pluralism; Repression; Human Rights; Social integration; Migration policies; framings; social discrimination; state capacities; frames; policymaking; language; Visible; Component; Universe; Unrealistic; Lived experiences; Implementation; Matatag Curriculum; upland areas; public-school teachers